‘O breves et infaustos populi favores’. The Controversies Surrounding Lieutenant Władysław Gorzeński during the Civil War in Poland-Lithuania (1715–1716) - Marcin Różycki (Theatrum Historiae)
On 1st October 1715 Władysław Gorzeński became the first marshal of the soldiers’ union which began to fight against the Saxon forces of King Augustus II on Polish-Lithuanian territory, thereby unleashing a civil war between the monarch, supported by various officials, and the Polish-Lithuanian army alongside the masses of civilian nobility, united under the Tarnogród Confederation. Gorzeński is considered to be a man with numerous controversies surrounding his actions at that time. As a low-ranking officer whose career to that point had not been particularly eventful or scintillating, he surprisingly managed to take control over his unit from his superior – the historical sources known to us describe that entire situation as, at the very least, confusing. Later, as he was leading his forces against the Saxon, he displayed serious incompetence which led to various accusations of intentional sabotage and eventually almost made him a victim to a lynch mob. Having given up his command in the union after a mere two months, he was forced to seek protection among those who had recently been enemies. The purpose of the article is to discuss contemporary opinions, according to which Gorzeński was indeed an agent of the Saxons and a provocateur supposed to trigger the civil conflict into escalation and compare them with facts and sources which bring up a quite different picture of the person in question – a victim of a slander and anti-Saxon paranoia the most of the Confederation was succumbing to at the time.